Comprehensive Atlas of Dermatoscopy Cases (Springer International Publishing, 2018)
This practical atlas describes the use of dermoscopy in the clinic, a technique that is increasingly used by the clinical dermatologist. It revolves around the use of clinical cases, simulating what happens in in the clinic when the dermatologist is presented with a patient who has pigmented lesions. Dermatologists perform diagnoses based on what they see on the skin and with these images recognize different diseases. This whole spectrum of forms and shapes is reflected in colour. Dermoscopy opens a new and very wide field of structures and colors that can not be seen with the naked eye and, with appropriate training and the use of this book, improves our clinical diagnosis. Comprehensive Atlas of Dermatoscopy Cases teaches the technique through specially selected clinical cases that cover the entire field of dermoscopy, providing the reader a thorough understanding of the techniques and methodologies associated with diagnosis using dermatoscopy. It is of great use to the trainee dermatologist and any practicing dermatologist seeking to expand their skills with this important diagnostic tool.